Limited Applicability of GW9662 to Elucidate PPARγ-Mediated Fatty Acid Effects in Primary Human T-Helper Cells - Anke Jaudszus; Stefan Lorkowski; Michael Gruen; Alexander Roth; Gerhard Jahreis (Hindawi Limited, 2014)
Synthetic antagonists of the nuclear receptor PPARγ such as GW9662 are widely used to elucidate receptor-mediated ligand effects. In addition and complementary to recent work, we examined whether GW9662 is suitable to serve for mechanistic investigation in T-helper cells. Human peripheral blood mononuclear cells (PBMC) were preincubated with increasing concentrations of GW9662 (0, 0.4, 2, and 10 μmol/L) 30 min before adding the c9,t11-isomer of conjugated linoleic acid (c9,t11-CLA) as representative of PPARγ-activating fatty acids with immunomodulatory properties. Corresponding cultures were incubated with GW9662 in the absence of the fatty acid. After 19 h, cells were mitogen stimulated for further 5 h. Subsequently, intracellular IL-2 was measured in CD3+CD4+ lymphocytes by means of flow cytometry. 100 μmol/L c9,t11-CLA reduced the number of T-helper cells expressing IL-2 by 68%. GW9662 failed to abrogate this fatty acid effect, likely due to the fact that the compound exerted an own inhibitory effect on IL-2 production. Moreover, GW9662 dose-dependently induced cell death in human leukocytes. These results suggest that application of GW9662 is not conducive in this experimental setting.